HYGIENE DAN SANITASI DI THE 18th KITCHEN THE TRANS LUXURY HOTEL BANDUNG - Dimas Setio Kresnadi; Rian Andriani (LPPM Universitas Bina Sarana Informatika, 2014)
Abstract - Kitchen is a food processing center at the hotel. Good and bad food products in hotel determined on Personal hygiene, sanitation food, sanitation equipment, and sanitary environment in the hotel kitchen is well organized. Hygiene and sanitation in the kitchen is essential to produce healthy food and clean, this study found that poor personal hygiene are employees who are less aware of hand hygiene, food storage facilities that do not match the standard, not the availability of ultraviolet sterilization box for kitchen Utensil, sewerage is inadequate and the use of non-sterile rubber carpet. The research method used in this research is descriptive method. Based on the data obtained, the management should improve the standard of hygiene and sanitation in the kitchen by providing training routine personal hygiene, and keep adding to the food storage bins, providing ultraviolet Utensil box for the kitchen, replacing the flooring with anti slip floor and improve drainage waste according to the standard. Keywords: Hygiene, Sanitation in kitchen hotel Abstrak - Kitchen merupakan pusat pengolahan makanan di hotel. Baik buruknya produk makanan di hotel ditentukan pada Personal hygiene, sanitasi makanan, sanitasi peralatan, dan sanitasi lingkungan di kitchen hotel yang teratur dengan baik. Hygiene dan sanitasi di kitchen sangatlah penting untuk menghasilkan makanan yang sehat dan bersih, dalam penelitian ini ditemukan personal hygiene yang kurang baik yaitu karyawan yang kurang sadar akan kebersihan tangan, tempat penyimpanan makanan yang tidak sesuai standar, tidak tersedianya ultraviolet box untuk sterilisasi kitchen utensil, saluran pembuangan air limbah yang kurang memadai dan penggunaan karpet karet yang tidak steril. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskriptif. Berdasarkan data yang diperoleh maka management sebaiknya memperbaiki standar hygiene dan sanitasi di kitchen dengan cara memberikan training rutin personal hygiene, menambah dan menjauhkan tempat penyimpanan makanan dengan tempat sampah, menyediakan ultraviolet box untuk kitchen utensil, mengganti lantai dengan lantai anti slip dan memperbaiki saluran pembuangan air limbah sesuai standar. Kata Kunci : Hygiene, Sanitasi di kitchen hotel